Interrelationships between Somatostatin sst2A Receptors and Somatostatin-Containing Axons in Rat Brain: Evidence for Regulation of Cell Surface Receptors by Endogenous Somatostatin - Dournaud, Pascal (J Neurosci, 1998)
Using an antipeptide antibody, we reported previously on the distribution of the somatostatin sst2A receptor subtype in rat brain. Depending on the region, immunolabeled receptors were either confined to neuronal perikarya and dendrites or distributed diffusely in tissue. To investigate the functional significance of these distribution patterns, we examined the regional and cellular relationships between somatostatin axons and sst2A receptors in the rat CNS, using double-labeling immunocytochemistry. Light and confocal microscopy revealed a significant correlation (p < 0.02) between the distribution of somatodendritic sst2A receptor immunoreactivity and that of somatostatin terminal fields, both quantitatively and qualitatively. Furthermore, in regions of somatodendritic labeling, a subpopulation of sst2A-immunoreactive cells was also immunopositive for somatostatin, suggesting that a subset of sst2A receptors consists of autoreceptors. By contrast, in regions displaying diffuse sst2A labeling only moderate to low densities of somatostatin terminals were observed, and no significant relationship was found between terminal density and receptor immunoreactivity. At the electron microscopic level, areas expressing somatodendritic sst2A labeling were found by immunogold cytochemistry to display low proportions of membrane-associated, as compared with intracellular, receptors. Conversely, in regions displaying diffuse sst2A receptor labeling, receptors were predominantly associated with neuronal plasma membranes, a finding consistent with the high density of sst2 binding sites previously visualized in these areas by autoradiography. Double-labeling studies demonstrated that in the former but not in the latter regions, sst2A-immunoreactive somata and dendrites were heavily contacted by somatostatin axon terminals. Taken together, these results suggest that the low incidence of membrane-associated receptors observed in regions of somatodendritic sst2A labeling may be caused by downregulation of cell surface receptors by endogenous somatostatin, possibly through ligand-induced receptor internalization.